2013
DOI: 10.1111/iju.12238
|View full text |Cite
|
Sign up to set email alerts
|

Recent status of the treatment of stress urinary incontinence

Abstract: Abbreviations & AcronymsAbstract: The therapeutic options for management of stress urinary incontinence can be conservative, pharmacological or surgical. The treatment of patients with stress urinary incontinence should be tailored to the individual to optimize care. A multitude of surgical techniques have emerged to treat this condition in recent years. The objective of the present review was to present an overview of current practice in the management of stress urinary incontinence while considering the evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 69 publications
(118 reference statements)
0
17
0
Order By: Relevance
“…Therapeutic targets for the treatment of SUI include serotonergic and adrenergic receptors in the spinal cord as well as adrenergic receptors within the urethral sphincter . Duloxetine, a serotonin and noradrenaline reuptake inhibitor, has been approved for the treatment of moderate to severe SUI in women in the European Union but not in the United States or Japan . Thus, new drugs, specifically designed to act on the therapeutic receptor targets for SUI, are desirable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therapeutic targets for the treatment of SUI include serotonergic and adrenergic receptors in the spinal cord as well as adrenergic receptors within the urethral sphincter . Duloxetine, a serotonin and noradrenaline reuptake inhibitor, has been approved for the treatment of moderate to severe SUI in women in the European Union but not in the United States or Japan . Thus, new drugs, specifically designed to act on the therapeutic receptor targets for SUI, are desirable.…”
Section: Discussionmentioning
confidence: 99%
“…Duloxetine, a serotonin and noradrenaline reuptake inhibitor, has been approved by the regulatory agency in the European Union for the treatment of moderate to severe SUI in women . In clinical trials, duloxetine has demonstrated efficacy in reducing incontinence episodes and increasing the quality of life with no serious adverse events in women with SUI .…”
Section: Introductionmentioning
confidence: 99%
“…No trials were available for inclusion in the review that support the sustainability of the benefits of duloxetine (Mariappan, Alhasso, Crant, & N'Dow, 2009). Duloxetine is not FDA-approved in the United States due to adverse events, including liver toxicity and suicidal ideations (Verghese & Latthe, 2013).…”
Section: Antidepressantsmentioning
confidence: 99%
“…Pelvic floor muscle training is usually the first line of management and is effective in approximately two-thirds of these women. However, for those requiring surgical treatment, a midurethral sling (MUS) such as the transobturator tape (TOT) procedure is currently the gold standard treatment for SUI, with high success rates (approximately 77-85 %) [1][2][3].…”
Section: Introductionmentioning
confidence: 99%